Research advances in the role of endogenous neurogenesis on neonatal hypoxic-ischemic brain damage - Andi Chen; Xiaohui Chen; Jianhui Deng; Xiaochun Zheng; Xiaochun Zheng (Frontiers Media S.A., 2022)
Hypoxic-ischemic brain damage (HIBD) is the main cause of perinatal mortality and neurologic complications in neonates, but it remains difficult to cure due to scarce treatments and complex molecular mechanisms remaining incompletely explained. Recent, mounting evidence shows that endogenous neurogenesis can improve neonatal neurological dysfunction post-HIBD. However, the capacity for spontaneous endogenous neurogenesis is limited and insufficient for replacing neurons lost to brain damage. Therefore, it is of great clinical value and social significance to seek therapeutic techniques that promote endogenous neurogenesis, to reduce neonatal neurological dysfunction from HIBD. This review summarizes the known neuroprotective effects of, and treatments targeting, endogenous neurogenesis following neonatal HIBD, to provide available targets and directions and a theoretical basis for the treatment of neonatal neurological dysfunction from HIBD.